STATE ACCOUNTABILITY TOWARDS CONSTITUTIONAL TORT IN THE IMPLEMENTATION OF THE FREE NUTRITIONAL MEAL PROGRAM IN INDONESIA - Muhammad Zafif Zulka; Muhammad Ghazi Alfaruqi Ilmi; Salsa Azza Nabilla (Journal of Governance and Law Reform, 2026)
This study aims to examine whether the implementation of the Free Nutritious Meal Program constitutes a constitutional tort and to analyze the forms of state responsibility arising from its implementation. The research employs a normative legal method using statutory, conceptual, comparative, and case approaches to assess the constitutional implications of the program. The findings indicate that the implementation of MBG has generated serious concerns, including mass food poisoning incidents caused by inadequate food safety standards and weak supervision, as well as the potential misallocation of education funds. These shortcomings demonstrate the state's failure to effectively fulfill its constitutional obligations to protect and guarantee the rights to health and education. Such failure may be classified as a constitutional tort, referring to violations of constitutional rights resulting from state action or omission. In this context, state accountability extends beyond administrative responsibility to encompass constitutional and legal liability. Therefore, the state is obligated to provide effective remedies for victims, including compensation where appropriate, strengthen monitoring and food safety mechanisms, and improve policy design and implementation to prevent similar constitutional violations in the future. These measures are essential to ensure that public welfare programs are implemented in accordance with constitutional principles and the protection of fundamental rights.